Implementing a trilineage differentiation in the ReproTracker assay for improved teratogenicity assessment - Horcas-Nieto, José M.; Hartvelt, Sabine; Flatt, Luke; Fang, Jing; Lam, Esther; Zhang, Gaonan; Van Vliet, Romy; Feliksik, Marleen; Zwetsloot, Tom; Philippo, Connor; Hendriks, Giel; Jamalpoor, Amer (Frontiers in Toxicology, 2025)
IntroductionExposure to teratogenic compounds during pregnancy can lead to significant birth defects. Given the considerable variation in drug responses across species, along with the financial and ethical challenges associated with animal testing, the development of advanced human-based in vitro assays is imperative for effectively identifying potential human teratogens. Previously, we developed a human induced pluripotent stem cells (hiPSCs)-based biomarker assay, ReproTracker, that follows the differentiation of hiPSCs into hepatocytes and cardiomyocytes. The assay combines morphological profiling with the assessment of time-dependent expression patterns of cell-specific biomarkers to detect developmental toxicity responses.MethodsTo further increase the predictability of the assay in identifying potential teratogens, we added differentiation of hiPSCs towards neural rosette-like cells. We evaluated the performance of the extended assay with a set of 51 well-known in vivo teratogens and non-teratogens, including the compounds listed in the ICH S5 reference list.ResultsThe optimized assay correctly identified (neuro)developmental toxicants that were not detected in the hepatocyte and cardiomyocyte differentiation assays. These compounds selectively downregulated gene and protein expression of the neuroectodermal marker PAX6 and/or neural rosette marker NESTIN in a concentration-dependent manner and disrupted the differentiation of hiPSCs towards neural rosette-like cells. Overall, based on the current dataset, the addition of neural commitment improved the assay accuracy (from 72.55% to 86.27%) and sensitivity (from 67.50% to 87.50%), when compared to the previously described assay.DiscussionIn summary, trilineage differentiation expanded the spectrum of teratogenic agents detectable by ReproTracker, making the assay an invaluable tool for early in vitro teratogenicity screening.